OPTIMIZATION OF SINGLY REINFORCED RC BEAMS - Thomas, Stency Mariam; Arulraj. G, Prince (International Journal of Research -GRANTHAALAYAH, 2017)
The main objective of this paper is to achieve an optimal design for the reinforced concrete beams. Optimization of beams results in saving in cost. The objective function is to minimize the total cost of the beam. The cost of each beam includes the cost of concrete, reinforcement and formwork. The optimization process is done for different grades of concrete and steel to determine the best grade of concrete and steel. The optimal design is carried out using MATLAB’s (The Mathworks, Inc.) software. Optimization problem is formulated as a Nonlinear constrained minimization problem. This was solved using the fmincon SQP Algorithm. Many problems were solved and it was found that the solutions give the most economical design.